2021
DOI: 10.3389/fpsyg.2021.707079
|View full text |Cite
|
Sign up to set email alerts
|

Stress of COVID-19, Anxiety, Economic Insecurity, and Mental Health Literacy: A Structural Equation Modeling Approach

Abstract: The COVID-19 pandemic is currently a global health threat attributed to negatively affecting the mental health and well-being of people globally. The purpose of the current study is to examine the mediating roles of economic insecurity and mental health literacy in the relationship between stress about COVID-19 and anxiety. Results from the current study using a large sample of Chinese college students (N = 1,334) showed that stress of COVID-19 was positively associated with economic insecurity and anxiety whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…were rated on a five-point scale (from 1 = never to 5 = very often). Applied to Chinese samples, the cultural adaption and reliability of the revised scale are well (70,71), and the validity of the revised scale is well (71)(72)(73). The goodness of fit [CFI = 0.91, TLI = 0.91, RMSEA = 0.08, 90% CI = (0.07, 0.09)] of confirmatory factor analysis of the Coronavirus Stress Scale in this study indicated that fit indicators in accordance with the cutoffs recommended in the literature actually showed a satisfactory adequacy, indicating that the scale had good construct validity.…”
Section: Instrumentsmentioning
confidence: 99%
“…were rated on a five-point scale (from 1 = never to 5 = very often). Applied to Chinese samples, the cultural adaption and reliability of the revised scale are well (70,71), and the validity of the revised scale is well (71)(72)(73). The goodness of fit [CFI = 0.91, TLI = 0.91, RMSEA = 0.08, 90% CI = (0.07, 0.09)] of confirmatory factor analysis of the Coronavirus Stress Scale in this study indicated that fit indicators in accordance with the cutoffs recommended in the literature actually showed a satisfactory adequacy, indicating that the scale had good construct validity.…”
Section: Instrumentsmentioning
confidence: 99%
“…Previous study have provided support for these assertions, low SES is signi cantly associated with high interparental con ict, and these adolescents may report higher emotional insecurity . Meanwhile, families with low SES are more likely to face even greater economic challenges during the COVID-19 pandemic: families in low-income urban areas in developing countries may face the risk of unemployment and other social barriers, which may increase the health and economic insecurity of adolescents (Haidar et al, 2021;Hu et al, 2021). Based on these multiple perspectives, we conclude that low SES is indeed an important risk factor for adolescents' psychological insecurity.…”
Section: Discussionmentioning
confidence: 83%
“…Besides, the assessment of insecurity of the environment was ampli ed during the COVID-19 pandemic; if infected with COVID-19, individuals in low SES families may not have enough nancial resources to tide them over (Haidar et al, 2021). Meanwhile, parents' unemployment and other social system barriers may cause adolescents to predict future turbulence in the family's economic situation, resulting in a greater sense of psychological insecurity (Hu et al, 2021). Adolescents would try to preserve their psychological security in a risk environment, which requires a large expenditure of psychological resources and limits their development .…”
Section: Psychological Insecurity As a Mediatormentioning
confidence: 99%
“…The Coronavirus Stress Measure (CSM) was adapted from the 14-item perceived stress scale [PSS], 45 to assess COVID-19 related to stress. The adapted CSM 46 , 47 in the study included 5 items with scoring based on 5-point Likert scale, ranging between 1 = never and 5 = very often (e g, “How often have you been upset because of COVID-19 in the last month”), Cronbach’s alpha (α) = 0.90. In the Cronbach reliability analysis, high reliability requires the value of alpha coefficient to be higher than 0.8, along with good reliability just requiring α being 0.7–0.8.…”
Section: Methodsmentioning
confidence: 99%